Results of determining essential breeding traits of a standard grain sorghum sample - V. F. Khlystunov; V. V. Kovtunov (Зерновое хозяйство России)
The selection of promising grain sorghum varieties according to the breeding results is complicated by the fact that it is necessary to take into account 49 characteristics (identiﬁers). This essentially multi-criteria comparison problem currently has neither a theoretical nor an unambiguous practical solution, which determines the relevance of the current study. The purpose of the study was to identify the essential characteristics (identiﬁers) and their scientiﬁcally based scoring of a standard grain sorghum sample based on the method of expert estimations. Based on the results of the expert estimation including leading specialists in grain sorghum breeding, there have been ranked 26 traits out of 49, provided for by the current international classiﬁer, which can be quantitatively digitized and which also reﬂect biological properties, morphological descriptors of the variety, its productivity, resistance to diseases, chemical composition, etc. After conducting a ranking procedure, estimation of the representativeness of the selection, the consistency of expert opinions and the non-accidentality of their agreement, there was carried out a structuring of the totality of statistical material (rank estimation) according to the integral function of the accumulated frequencies of each ranked feature’s appearance using the original author’s computer program. As a result, there have been identiﬁed 13 signiﬁcant (most signiﬁcant) estimation traits of grain sorghum, amounting to 64.1 % in terms of ranking and 50 % in terms of quantitative signiﬁcance. There was set up an estimation scale for them, based on their rank signiﬁcance on a 100-point scale for the standard grain sorghum sample (“Zernogradskoe 88” developed by the “ARC “Donskoy”). Based on the data of determining the signiﬁcance of the corresponding traits in physical terms of the compared and standard samples, as well as its score rating for the standard, there was established a point rating of the corresponding traits for the compared samples and complex estimation indicators as their sum. The complex indicator for the compared samples of the varieties ‘Ataman’ and ‘Esaul’ developed by the “ARC “Donskoy” was calculated in accordance with the share of each index relative to the standard one. Their quantitative comprehensive estimation was 111.43 and 101.93 points, respectively. Thus, these varieties exceeded the standard for a set of traits by 111.43 and 101.93 %, respectively.